TINDAKAN PENGHINDARAN PAJAK PADA PERUSAHAAN MANUFAKTUR DI BURSA EFEK INDONESIA - Silvia Hendrayanti; Wachidah Fauziyanti (JURNAL CAPITAL : Kebijakan Ekonomi, Manajemen dan Akuntansi, 2022)
Tax is a state levy on individuals or entities that is obligatory and coercive in nature which will be used by the state for the prosperity of the people but does not receive direct reciprocity. Tax avoidance is an arrangement to minimize or eliminate the tax burden by considering the tax consequences it generates, and not as a tax violation because the taxpayer's efforts to reduce, avoid, minimize or alleviate the tax burden are carried out in a way that allows for tax laws. This study aims to determine the effect of audit committees, audit quality, and sales growth on tax evasion. This research was conducted at manufacturing companies listed on the Indonesia Stock Exchange for the 2016-2020 period. The sampling technique used purposive sampling in order to obtain a sample of 135 companies. Methods of data collection using documentation. Data analysis technique using multiple linear regression analysis. z Based on the results of hypothesis testing shows that the significance of the auditor's committee is 0.000 <0.05, so that the auditor's committee has a significant effect on tax evasion. The significance of auditor quality is 0.288> 0.05, so that auditor quality has no significant effect on tax evasion. The significance of sales growth is 0.000 <0.05, so sales growth has a significant effect on tax evasion. The coefficient of determination shows a result of 0.281 or 28.1%. For future researchers, it is hoped that they can add research samples to other sectors in order to be able to describe the condition of the company as a whole regarding tax avoidance